Cognitive Function as Measured by Trail Making Test in Patients With COPD. (February 2015) - Park, Soo Kyung; Larson, Janet L.
People with chronic obstructive pulmonary disease (COPD) exhibit cognitive impairment in several subdomains, but little is known about factors associated with cognitive function and its relationship to health-related quality of life (HRQOL) in people with COPD. A data set from the National Emphysema Treatment Trial was used for this study. Data were obtained through questionnaires and clinical testing. Cognitive function in people with COPD was measured with the Trail Making Test. Descriptive and inferential statistics were used to analyze the data. Participants with COPD had slightly impaired processing speed and executive function. Test results revealed that age, gender, education, and income were significantly associated with cognitive function. Test scores also showed that cognitive function was significantly associated with HRQOL in people with COPD. This finding suggests that cognitive function should be screened in people with COPD.